Design of a compact and wide-band antenna for UAV system - Tan, Ji Tu (Nanyang Technological University, 2022)
This final year project details the design of a compact wideband antenna that will be used for Unmanned-Aerial-Vehicle (UAV) which will be operating in the frequency range of 400MHz to 1200MHz. The proposed antenna will be an omni-directional Monocone with shaped cap antenna. This report will be covering the entire process of the design procedures, software design, simulation of antenna and the steps taken to optimize the best results. Prior to deep diving into any of the mentioned coverage, basic information of the fundamental concepts of antenna will be shared. This is to ensure that readers have a clearer understanding and thus can relate better with the objective and drive behind this project. Intensive research is carried out to understand the various design parameters which are used to counter the constraints of building a compact wideband omni directional antenna. The Ansys High Frequency Structure Simulator (HFSS) software will be used to carry out the designing portion of the antenna. It consists of various specialised tools which can be used for design modification and simulation of designed antenna which enables us to compare with results derived from calculations. The Ansys HFSS is able to display various parameter settings of the designed antenna such as the S-Parameter, radiation pattern, Z-Parameter, gains etc. The simulated results after completion of the design deduced a good return loss and gains comparable to that of existing commercially available antennas that operates in a low frequency range. In summary, the design and simulation are all within a satisfactory margin comparing to that of a calculated theory scenario and can be utilised in an actual world application for the intended purpose.